UPAYA KONVERGENSI KEBIJAKAN PROGRAM ANTING BERLIAN (ATASI STUNTING BERIKAN KEPEDULIAN) DI KOTA BANJAR - Tofan Ibrahim; Nova Chalimah Girsang (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
This scientific article discusses convergence efforts in handling the stunting problem in Banjar City. Before the collaborative effort, Banjar City faced a stunting problem caused by an imbalance of resources and knowledge, a lack of understanding about health, nutrition and good parenting patterns. Convergence efforts involve various sectors such as health, food, education and society through the Anting Berlian program (Overcoming Stunting and Giving Care). The approach used in this research is qualitative with descriptive methods. The data sources used are primary data and secondary data. Data collection techniques through observation, documentation and interviews. The technique for determining informants uses purposive sampling. The results of the research explain the convergence efforts made by the Banjar City Government to reduce the stunting problem: coordination between the health sector and the food sector, integration of health and nutrition service programs, cross-sector approaches in education, involvement of communities and community organizations, multi-sectoral approaches in poverty alleviation, and strengthening information and monitoring systems.